Tate Report : Tate Gallery Biennial Report 1994-96. - Tate Gallery, London (London : Tate Gallery, 1996)
Adams, Robert ; Allington, Edward ; Araeen, Rasheed ; Arikha, Avigdor ; Ayres, Gillian ; Balka, Miroslaw ; Barney, Matthew ; Bevan, Tony ; Blamey, Norman ; Blow, Sandra ; Bomberg, David ; Bourgeois, Louise ; Brodzky, Horace ; Buckley, Stephen ; Chadwick, Helen ; Clark, Thomas A. ; Clarke, Geoffrey ; Cohen, Bernard ; Collins, Cecil ; Collins, Hannah ; Coplans, John ; Cragg, Tony (Anthony) ; Craxton, John ; Cross, Dorothy ; Davey, Grenville ; Davis, Stuart ; Doig, Peter ; Eates, Margot ; Epstein, Sir Jacob ; Eyton, Anthony ; Francis, Mark ; Freud, Lucian ; Fuller, Peter ; Gabo, Naum ; Giacometti, Alberto ; Gill, Eric ; Gordon, Max ; Gormley, Antony ; Graham, Paul ; Gross, Anthony ; Guevara, Meraud ; Gursky, Andreas ; Halliday, Edward ; Hambling, Maggi ; Finlay, Ian Hamilton ; Hamilton, Richard ; Hatoum, Mona ; Hennell, Thomas Barclay ; Hepworth, Barbara ; Hiller, Susan ; Himid, Lubaina ; Hockney, David ; Horsfield, Craigie ; Hoskin, John ; Howson, Peter ; Immendorff, Jörg ; Indiana, Robert ; Innes, Callum ; Jones, David ; Kelly, Ellsworth ; Kinley, Peter ; Koenig, Ghisha ; Koons, Jeff ; Kossoff, Leon ; Lanyon, Peter ; Lessore, John ; Lett-Haines, Arthur ; Lichtenstein, Roy ; Long, Richard ; Malinowski, Antoni ; Martini, Arturo ; May, Nicholas ; McKeever, Ian ; McKenna, Stephen ; Medley, Robert ; Meninsky, Bernard ; de Monchaux, Cathy ; Moody, Ronald ; Morris, Sir Cedric ; Motherwell, Robert ; Muñoz, Juan ; Murphy, Myles ; Nash, John ; Nash, Paul ; Nauman, Bruce ; Neiland, Brendan ; Newman, Barnett ; Nicholson, Ben ; Nicholson, Winifred ; Ono, Yoko ; Ortman, George ; Oursler, Tony ; Paolozzi, Eduardo ; Parker, Cornelia ; Pasmore, Victor ; Picasso, Pablo ; Poons, Larry ; Ramsden, E.H. ; Randall-Page, Peter ; Redo, Achill ; Rego, Paula ; Reinhardt, Ad ; Richier, Germaine ; etc.
Biografie
Contents: Achievements of the Biennium ; Tate Gallery St Ives ; Tate Gallery Liverpool ; Gifts to the Collection ; Acquisitions for the Collection 1994-96 ; loans ; exhibitions ; publications ; ...
Engels
boek